(3CMOGK GdLhs - (3jYbhH Hf ESMGb Hf GdUHGM GdcfOj, CHh jhSa,J (B260 (3g` s
(3ChdgG (B:s
(3Ef GdOdjd GdChd Ydi eG MOK ai GdLh ef MQ Ch HQO ChQWhHI ChjHS , ef RMd hGdeTJQi ; dCf RMd Odd Cfg gh hGdeTJQi Odjd GdSfI s
(3BNQgG (B:s
(3GdJZjQ GdYGQV dcd GdLh ai cd ehVY Ydi bOQ fSHI ReGfg aCeG GdOdjd GdLRFi , dcd ehVhY aGJQ GdeeRhL HgPg GdTgGOGJ JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B147(3H (B- (3U(B149(3Cs
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B244s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B230 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B372 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs